PETROLOGY, GEOCHEMISTRY AND GEOTECTONIC SETTING OF THE TITAROS OPHIOLITE AND ASSOCIATED PELAGONIAN BASEMENT ROCKS IN THE AREA NW OF MT. OLYMPOS, GREECE - Boudi, D.; Prophitis, E.; Zachariadis, P.; Kostopoulos, D.; Baltatzis, E.; Chatzitheodoridis, E. (Bulletin of the Geological Society of Greece, 2007)
The Titaros ophiolite in Greece is a coherent thrust sheet of oceanic rocL· that lies atop Permo-Carboniferous granitic orthogneisses and amphibolites of unknown age of the eastern Pelagonian margin in the area NW of Mt. Olympos. It comprises a harzburgite tectonite mantle sequence with chromite mineralisation and a welldeveloped magma chamber with cyclic units ofdunite-lherzolite-wehrlite-pyroxenite that pass upwards into massive gabbros cut by diabase dykes and locally containing plagiogranite ponds. Ophiolite mineral and whole-rock chemistry are strongly in favour of a supra-subduction zone origin in a purely oceanic setting with the occasional brawny signature of melts from subducted sediments. By contrast, the basement amphibolites display a clear within-plate tholeiitic affinity with a slight imprint of subduction-zone fluids. Mineral stretching lineations and kinematics indicators of the orthogneisses and amphibolites suggest a consistent transport direction to the WSW. It is proposed that the basaltic protoliths of the amphibolites were emplaced during Permo-Triassic rifting of the eastern Pelagonian margin that led to the subsequent formation of the Vardar Ocean. The Titaros ophiolite was formed during closure of the Vardar Ocean via northeast-directed intra-oceanic subduction and subsequent obduction towards the southwest onto the eastern Pelagonian margin, probably in the Lower Cretaceous.